Reading Comprehension of Analytical and Hortatory Exposition: A Comparative Study - Maulya, Ranti; Kamarullah, Kamarullah (EDUJ : English Education Journal, 2023)
Reading has become one of the compulsory skills taught in schools and it is one skill which is tested in National Examinations in Indonesia. The needs to comprehend texts, particularly expositional ones, are indispensable. Therefore, this study has an objective to find out the significant differences in students’ evaluation of reading skills and generic structure in analytical and hortatory exposition. After calculating the data using a statistical application, SPSS, we obtained a significant difference in the second-grade students’ evaluation of MAN Darussalam Aceh Besar in analytical and hortatory exposition based on reading comprehension skills. It can be shown that Tcount is higher than Ttable (3.490 > 2.101). There is also a significant difference in students’ evaluation of detailed information and vocabulary skills. Most students had difficulties in answering inference questions. The calculation result of the generic structure of analytical and hortatory exposition shows no significant difference in the second-grade students’ evaluation of Analytical and Hortatory exposition. It can be demonstrated that Tcount (-1.500) is lower than Ttable (2.101). The generic structure comparison table between analytical and hortatory exposition showed no significant difference in students’ evaluation of the second-grade students in identifying the generic structure of the texts. Still, the students scored the lowest in identifying analytical exposition conclusions and hortatory exposition suggestions.